Art across the curriculum : pedagogical principles to inform teaching - Kean, Rexford C., 1969- (1996)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1997. Education Bibliography: leaves 82-85. This project has been developed to inform teachers of a set of pedagogical principles which may be used to teach art across the curriculum. It is written from the perspective of arts educators and consequently views education as being holistic. -- The initial conception of this work originated from the elementary classroom, where students explored various subject areas using a thematic approach. Being an art teacher with elementary classroom duties, I incorporated art into the regular curriculum thus involving art education in the process of teaching and learning. -- A survey of relevant literature has been conducted for this project and has aided in formulating the direction for the field research component. The field research which underpins this work has been conducted in Harlow, England over a six week period. It was composed of six interviews, using six questions, to investigate the current views of arts educators from all levels of teaching. The six areas are generated from the Burlak Dilemmas, as stated in Miller and Seller (1990). They deal with educational aims, conception of the learner, conception of the learning process, conception of the learning environment, conception of teacher role, and conception of the evaluation process. An analysis of current literature and the field interviews was used as a platform to inform my emergent pedagogical principles of art across the curriculum. The results of this work, therefore, produce a set of pedagogical principles informing educators of the philosophy of art across the curriculum.